Preparation to Old Age as the Task of Some People and Communities - Krzysztof Juszczak (Pedagogical Discourse, 2012)
The demographic phenomenon of the aging of the Polish society, in addition to a clear increase in interest in the period of old age, both in the individual aspect and from the social point of view, is associated with the need to intensify efforts to prepare for old age. Long-term neglect in education for old age strengthens negative behaviors in the elderly. Hence, one should look for ways leading to a change of one's own (present or future) living space for the better, ways leading to old age in its desirable essence. The aim of this is to show preparation for old age as an essential task of individuals and collectivity. In addition, the author hopes that the content presented in the study will give rise to thoughts about the readiness for Poles and Poles to shape their own future, and above all, readiness to take responsibility for themselves in old age.